2022
DOI: 10.1021/acsaem.2c00470
|View full text |Cite
|
Sign up to set email alerts
|

Universal Deposition Strategy of Nanoporous Complex Oxide Thin Films for Photoelectrochemical Applications

Abstract: Developing facile approaches to prepare well-designed semiconductor nanostructures is an important goal for solar water splitting. Herein, a general solution method is reported that employs citrate to complex diverse metal cations and affords uniform nanoporous multiple oxide thin films with controllable porosity by spray pyrolysis. By using CuBi2O4 as a model material, a remarkable improvement in internal quantum efficiency and the impacts of the morphology on photoelectrochemical (PEC) performance is demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Spray pyrolysis is another adaptable synthesis process that is commonly used to produce nanoporous oxides ( e.g. , aluminum oxide, 170 iron oxide, 171–173 tin oxide, 174,175 titanium oxide, 176 ruthenium oxide, 177 vanadium oxide, 178 copper-bismuth oxide, 179 cerium oxide 180 ) based on thermal degradation of a liquid sample. In typical spray pyrolysis shown in Fig.…”
Section: Synthesis Of Nanoporous Oxidesmentioning
confidence: 99%
“…Spray pyrolysis is another adaptable synthesis process that is commonly used to produce nanoporous oxides ( e.g. , aluminum oxide, 170 iron oxide, 171–173 tin oxide, 174,175 titanium oxide, 176 ruthenium oxide, 177 vanadium oxide, 178 copper-bismuth oxide, 179 cerium oxide 180 ) based on thermal degradation of a liquid sample. In typical spray pyrolysis shown in Fig.…”
Section: Synthesis Of Nanoporous Oxidesmentioning
confidence: 99%
“…Herein, spinel‐type cobalt–iron oxide thin films have been prepared on FTO by our recently developed ultrasonic spray pyrolysis deposition route. [ 46 ] An extraordinary OER stability and improved activity in the neutral electrolyte can be achieved with a spinel‐based structure with an optimal Fe content of Co 0.7 Fe 0.3 . Structural characterizations indicate the improvements shall be attributed to the suitable distribution of Fe 3+ and Fe 2+ in both octahedral and tetrahedral sites of the spinel lattice.…”
Section: Introductionmentioning
confidence: 99%
“…These structures could be synthesized by the hydrothermal method, 6 sol−gel method, 10 spray pyrolysis method, and so forth. 11 Especially, one-dimensional TiO 2 nanotubes prepared by anodization, characterized by easy recycling, possess a high specific surface area and unidirectional electron transmission channels. This contributed to the optical absorption and reduce recombination of photogenerated carriers to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations revealed that the construction of suitable Ti-based nanostructures (nanorods, , nanosheets, and nanoflowers) could promote optical absorption and provide more active sites for oxygen evolution. These structures could be synthesized by the hydrothermal method, sol–gel method, spray pyrolysis method, and so forth . Especially, one-dimensional TiO 2 nanotubes prepared by anodization, characterized by easy recycling, possess a high specific surface area and unidirectional electron transmission channels.…”
Section: Introductionmentioning
confidence: 99%